2004
DOI: 10.2466/pr0.95.2.393-406
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Character Inventory in Homicidal, Nonaddicted Paranoid Schizophrenic Patients: A Preliminary Study

Abstract: This study assessed the personalities of 13 murderer schizophrenics using Cloninger's Temperament and Character Inventory, controlling different factors such as institution, treatment, detention or loss of liberty, and can discriminate between schizophrenic patients involved in homicide, schizophrenics with no past violent behavior, paranoiac murderers, and imprisoned murderers with no psychiatric history. Results show significantly that murderer schizophrenics had significantly higher scores on the subscale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Relatively fewer studies have reported similar findings in schizophrenia patients [74], with slight variations. [38,39], while schizophrenia patients with high Novelty Seeking are considered to be more impulsive, and likely to engage in aggressive response and inappropriate extroverted behaviors [35,36,76,77].…”
Section: Discussionmentioning
confidence: 87%
“…Relatively fewer studies have reported similar findings in schizophrenia patients [74], with slight variations. [38,39], while schizophrenia patients with high Novelty Seeking are considered to be more impulsive, and likely to engage in aggressive response and inappropriate extroverted behaviors [35,36,76,77].…”
Section: Discussionmentioning
confidence: 87%
“…Un diagnostic de trouble de la personnalité serait fréquemment retrouvé chez les malades mentaux violents [89], et il s'observerait chez les schizophrènes hostiles [4], violents [86], ou homicides [98], et notamment chez les personnalités paranoïaques ou narcissiques [70]. Néanmoins, parmi les troubles de la personnalité les plus fréquents dans le comportement violent chez les schizophrènes, on retrouverait la personnalité antisociale [56].…”
Section: Schizophrénie Et Trouble De La Personnalitéunclassified
“…Hare and Hart (1993) reviewed the literature and concluded that psychopathic traits predict violence even among those with psychosis. Vandamme and Nandrino (2004) assessed the personalities of 13 murderer schizophrenics controlling different factors such as institution, treatment, detention or loss of liberty, and can discriminate between schizophrenic patients involved in homicide, schizophrenics with no past violent behaviour, paranoiac murderers, and imprisoned murderers with no psychiatric history. They found that murderer schizophrenics had significantly higher scores on the subscale, self-transcendence than other groups which suggests that self transcendence as measured may be an aggravating factor for schizophrenic subjects who performed homicidal acts.…”
Section: Introductionmentioning
confidence: 99%